IMPLEMENTATION OF ACADEMIC SUPERVISION BY THE MADRASAH PRINCIPAL TO IMPROVE TEACHERS’ INSTRUCTIONAL ADMINISTRATION: A QUALITATIVE CASE STUDY AT MAN SERDANG BEDAGAI - Mujhirul Iman; Tamimi Mujahid; Anri Naldi; Hotni Sari Harahap; Muhammad Faisal (Yayasan Amanah Nur Aman, 2026)
This study examines the implementation of academic supervision by the madrasah principal in improving the quality of teachers’ instructional administration at MAN Serdang Bedagai. A qualitative single-case study design was employed. Eight key informants were selected purposively, comprising the madrasah principal, the vice principal for curriculum affairs, a member of the academic supervision team, and five teachers. Data were collected through semi-structured interviews, non-participant observations, and document analysis and were analysed using reflexive thematic analysis. The findings generated five major themes: systematic but flexible supervision planning, integration of instructional-document review with classroom observation, collaborative supervisory feedback, improvement in teachers’ instructional administration, and limitations in follow-up sustainability. Academic supervision contributed to improvements in teaching modules, assessment rubrics, teaching journals, and remedial and enrichment programmes, particularly by strengthening the alignment among learning objectives, instructional activities, assessment, and classroom practices. Teachers responded more positively when feedback was delivered through professional dialogue rather than fault-finding evaluation. However, limited written recommendations, overlapping schedules, supervisors’ workload, teachers’ administrative responsibilities, and inconsistent follow-up reduced the sustainability of the improvements. The study concludes that academic supervision is most effective when implemented as a continuous cycle of planning, observation, feedback, revision, and monitoring. Madrasah principals should therefore strengthen written feedback, differentiated professional assistance, and systematic follow-up to ensure that improvements in instructional administration are consistently reflected in classroom instruction.